Using Awards Excellence Models in Assessing Supply Chain Management Systems: A case study in the Plants of General Company of Leather Industries - Eslam Talib Aljabi (International Journal of Supply Chain Management, 2019)
This research is aimed to test and apply the concept of excellence awards of quality, according to the awards models of criteria to assess the extent of the application of quality management systems. A group of awards adopted by international, regional and local organizations means, outstanding administrative systems to evaluate performance and follow-up measuring their self-performance to reach excellence. The quality awards standards are of the most important methods of measuring performance, it has been access to a set of standards to achieve them. According to the present research the General Company for Leather Industries determined as industrial organization working for the public sector. The present study population for this research focused on testing those common standards and the extent of its contribution to the achievement of excellence in Organizational performance. The important elements used are Leadership, Strategic planning 'Human Resources, Resource management, Relationship with Partners, Processes, Focusing on the beneficiary, Impact on workers, Impact on the community, Evaluate the results of performance, Information, and the availability of such standards. The present study relied on the analytical method and results, some conclusions are made. Notably that awarded quality and organizations excellence in the field of quality and helps to spread the culture of quality. It was the most important recommendations that the Organization select their targets according to company policy and follow-up to achieve them and review the senior management to check the level of performance and attention to the management of operations and human resources and encourage them to work as a team continued excellence.